Antibacterial Activity of Glochidiol from Glochidion eriocarpum Enhanced Tetracycline against Opportunistic Bacteria - Kongcharoensuntorn, Wisatre; Warut , Warut (Burapha Science Journal, 2026)
The various biological activities of pure compound, Glochidiol from Khrai mot (Glochidion eriocarpum) are anti-inflammatory, anti-cancer and anti-microbial activity. In this study, synergistic effect of Glochidiol against opportunistic bacteria and drug-resistant gram negative bacteria was investigated. The Minimal Inhibitory Concentration (MIC) value and Fractional Inhibitory Concentration Index (FICI) were determined for synergistic effect by Broth diffusion test. Among eleven tested bacteria, Glochidiol alone showed the best antibacterial activity to inhibit the growth of B. subtilis and Methicillin-resistant S. aureus (MRSA) and had MICs equal as 128 µM. However, Glochidiol showed no antibacterial activity against drug-resistant Acinetobacter baumannii, Proteus mirabilis, P. vulgaris and drug-resistant P. aeruginosa. Moreover, combination of Glochidiol with tetracycline showed partially synergistic effect against E. coli ATCC 25922 and P. aerugiosa ATCC 27853 with FICI of 0.5156 and 0.5313, respectively. On the other hand, Glochidiol mixed with ampicillin had no effect against E. coli ATCC 25922, P. aeruginosa ATCC 27853. Then, Time-kill assay were tested and indicated that the specific times, mostly decreased the growth of E. coli ATCC 25922 and P. aerugiosa ATCC 27853 were at 4 and 6 hours after treatment with ½ MICs of tetracycline and 1/32-1/64 MICs of Glochidiol, respectively.